«Indo-European verbal designations of the concept «house, settlement» in the book of Movses Khorenatsi «History of Armenia»» - Dilbaryan, Narine (Bulletin of Yerevan University B: Philology, 2025)
Linguistic conceptology is a modern independent discipline that studies the features of the content of two-dimensional linguistic units, in particular, words, and the specified plans of expression and content can have a very broad understanding, that is, a word can be considered both as an ideological symbol, and as a universal object code, and as a lexical and grammatical field. Verbal designations of concepts in each language xpress the national and cultural features of thinking and worldview of the community speaking this language, which can undergo individual changes at different times, but are characterized by a certain stability. In this article, we examined various linguistic meanings of the concept of « settlement, house» in the famous work of the 5th century «History of Armenia» by Movses Khorenatsi, highlighting the Indo-European units of this concept, diachronically studying their semantic content from Ancient Armenian to Modern Eastern Armenian. In the book «History of Armenia» we identified about 55 words of indigenous, Indo-European origin, which in one way or another express ideas about the concept of « settlement, house» in the Ancient Armenian language, identified their semantic and word-formation characteristics, phonetic features, historical changes in the modern Armenian language. The lexical units of the concept we studied relate to the basic vocabulary, have a high frequency of use. Both common and proper names, phraseological units were studied.